PERSONAL AND MOTIVATION CRITERIA DEVELOPMENT OF MASTERS IN PRIMARY EDUCATION TO INNOVATIVE ACTIVITIES - Tsiuniak Oksana (Borys Grinchenko Kyiv Metropolitan University, 2020)
The article is devoted to the actual problem of professional preparation of future masters of elementary education for innovative activity. The author points out that the realities of the modern world, the transformation processes in the education system, the social procurement of the labor market encourage the revision of certain established views on the goals and objectives of higher education in general and the professional training of future masters of elementary education in particular. In this regard, there is a need to organize a system that would provide a purposeful process of forming the masters' professional readiness for innovation activity. The study of this process allowed us to identify the main components of masters' professional readiness for a specific activity, such as cognitive, motivational, reflexive, praxeological. In the context of the of the study, the motivational component determines the formation of motives for innovation as a pledge of self-realization and self-development of undergraduates; interest in innovation as an important source of professional needs, personal growth, a strong interest in creativity and more. In the article the level of the personality-motivational criterion is: conscious attitude of future masters of elementary education to innovative activity; formation of motives for professional self-improvement and self-development; stable orientation on humanistic values in pedagogical innovative activity; formation of professionally significant personality traits; the need for innovation; formation of creative potential; professional mobility. In the article the level of formation of personality-motivational criterion (motivational component) of professional readiness of future masters of elementary education for innovative activity at the indicative stage of the experiment is analyzed.